Geopolimer Berbasis Abu Terbang (Fly Ash) Boiler Pabrik Pulp Dengan Penambahan Grafena Oksida - Setiani Br Manurung; Amun Amri; Syamsu Herman (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Geopolymer has been successfully synthesized from boiler fly ash with the addition of Graphene Oxide (GO). The addition of graphene oxide is to enhance the mechanical properties of organicfly ash based geopolymer. Graphene oxide was made by using graphite from used batteries via Hummer method. The resulting graphene oxide solution was mixed with an alkaline activatorsolution (NaOH and Na2Si2O3) and stirred with a mixture of fly ash and sand. Once homogeneous, it was then poured into the mold and heat treated at temperature 900C for 24hours. A compressive strength test was performed using material testing equipment. The experiment results showed that the compressive strength of geopolymer with addition of GO wasincrease 44,67% in comparison with the geopolymer without GO. This results is very exciting to upgrade the quality of organic fly ash based geopolymer to reduce the use of conventionalcement due to of high carbon emission/polutant of conventional cement. In addition, this research can also reduce the abundant fly ash waste and overcome the accumulation of used batteries.Keywords: compressive strength, geopolymer, graphene oxide, hammer, fly ash